Change of Several Plant Nutrient Elements by Plant Species and Organ - Erdem, Ramazan (Turkish Science and Technology Publishing (TURSTEP), 2021)
Nutrient elements, one of the major factors shaping plant development, are the major components of plants, and, after being taken from the soil, they are present in different organs of plant at different concentrations. The speciation of nutrient elements within plant body is vital importance for determining the contribution to plant development, knowing the transfer between organs within the body of organs, clearly understanding the factors influencing plant development, and shaping the plant development. In the present study, the change of the concentrations of K and Mg (macronutrient elements) and Cu (micronutrient elements) by species and organ in woody species Prunus cerasifera, Platanus orientalis, Acer negundo, Fraxinus excelsior, Catalpa bignonioides, Aesculus hippocastanum, and Tilia platypyllos. As a result, it was found that the changes of elements by species were statistically significant in all the organs, and, in general, the highest concentrations were observed in leaves. The study results revealed that the concentrations of these elements might significantly vary between the organs in the same species, which varies significantly by the species.
Keywords: S; Agriculture (General); Agriculture; S1-972; 2. Zero hunger; 15. Life on land